THE IMPLEMENTATION OF FABLE STORY AS NARRATIVE TEXT MATERIAL TO IMPROVE STUDENTS READING COMPREHENSION AT SEVENT GRADE OF SMP KRISTEN SONDER - Rau, Ariane Grisenda; Pelenkahu, Noldy; Kumayas, Tirza A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The main focus of this study was on the understanding of students at the factual and analytical levels. The pre-experimental research approach employs pre-test and post-test as research instruments. The study sample comprised 73 students from SMP Kristen Sonder. The results indicated that students showed improvement, as seen by the average scores of the pre-test and post-test. The average pre-test score for literal understanding was 41.00%, however for interpretive comprehension it was 46.00%. Following the administration of therapy, the mean score for literal understanding showed a significant rise of 66.00%, while the mean score for interpretative comprehension exhibited a notable increase of 72.00%. The results of the significance test suggest that there is a notable disparity in reading comprehension between the literal and interpretive emphasis. The t-test value for the literal emphasis is 27,386, which exceeds the crucial value of 2,064. Moreover, the t-test value for the interpretative focus is 20,663, which exceeds the crucial limit of 2,064. It is utilized to verify the hypothesis that emerges in this inquiry. The null hypothesis (H0) was rejected because it lacked statistical significance, while the alternative hypothesis (H1) was accepted. The conclusion was made based on the t-test results, which showed that both literal comprehension (27,386) and interpretative comprehension (20,663) had values higher than the critical t-table value (2,04W2). The study revealed that students’ reading comprehension, specifically in the areas of literal and interpretative reading, shown improvement while utilizing fable stories